COST EFFECTIVENESS ANALYSIS PADA PERAWATAN GAGAL GINJAL DENGAN METODE HEMODIALISIS DAN PERITONEAL DIALISIS (Studi Kasus pada RSUP Dr Sardjito Yogyakarta) - , NIKEN K SAPTONO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this study is to evaluate treatment method for renal failure patient that give more effective result between hemodialysis and peritoneal dialysis treatment in Dialysis Instalation, RSUP Dr. Sardjito Yogyakarta. This study using Cost Effectiveness Analysis (CEA). Effectiveness measured by compare the result of cost per outcome (Cost Effectiveness Ratio) between hemodialysis and peritoneal dialysis treatment. This study was conducted by collecting primary data from 30 respondents of hemodialysis patient and 8 respondents of peritoneal dialysis patient. The data was collected by interview with key informants and using EQ-5D questionnaire to measured patientâs health condition. The result show that peritoneal dialysis give better health condition (0,913375) than hemodialysis (0,5879) even it need more money to spend for the treatment (Rp. 99.425.000,- per patient per year) than hemodialysis (Rp. 66.609.675,- per patient per year). Hemodialysis have CER 22.660.205,82 and peritoneal dialysis have CER 21.770.904,61. The conclusion is peritoneal dialysis more effective than dialysis treatment.